International Economic Activities and the Demand for Skilled labor: Evidence from Brazil and China - Fajnzylber, Pablo; Fernandes, Ana M. (World Bank, Washington, D.C., 2013)
Increases in international economic integration can lead to greater specialization according to comparative advantage, but also to the diffusion of skill-biased technologies. In developing countries characterized by relative abundance of unskilled labor, these factors can have opposite effects on the relative demand for skilled labor. This paper investigates the impact of the use of imported inputs, exports and foreign direct investment on the demand for skilled workers of Brazilian and Chinese manufacturing plants. We find that while in Brazil increased levels of international integration are associated with an increased demand for skilled labor, the opposite is true in China.